The Effect Of Giving A Combination Of Ginger (Zingiber Officinale Var. Amarum) And Lemongrass (Cymbopogon Citratus) Brewing In Overcoming Emesis Gravidarum In Pregnant Women In The First Trimester - Meilinda, Vittria; Marhamah, Marhamah (Institute Of Computer Science (IOCS), 2025)
Emesis gravidarum, commonly occurring during the first trimester of pregnancy, is characterized by nausea and vomiting that can lead to dehydration, nutritional deficiency, and psychological distress if left unmanaged. Herbal remedies, such as ginger (Zingiber officinale) and lemongrass (Cymbopogon citratus), are gaining attention for their effectiveness and minimal side effects in addressing this condition. In the Pangkalan Koto Baru District, out of 157 pregnant women, 149 reported experiencing nausea and vomiting, while 48 were diagnosed with Grade 1 hyperemesis gravidarum. Many of these women are generally unaware that natural remedies such as ginger and lemongrass can help alleviate these symptoms.This study aims to examine the effect of a ginger and lemongrass herbal drink in managing emesis gravidarum. The research employed a quasi-experimental design using a one-group pre-test and post-test method. It was conducted in the Pangkalan Koto Baru District with a target population of 77 first-trimester pregnant women. A sample of 30 participants was selected through purposive sampling. Data were analyzed using univariate and bivariate methods, with the Wilcoxon test applied due to the abnormal distribution of the data. The findings revealed a significant effect of consuming the ginger and lemongrass brew, with a p-value of 0.000. This study shows that ginger and lemongrass infusion can be a practical, low-risk alternative to reduce emesis gravidarum in first-trimester pregnancies. Its ease of use and natural properties make it suitable for community health settings. However, the small sample size, short intervention period, and uncontrolled external factors limit the generalizability of the results, indicating the need for broader and more controlled future research.